Reinforced magnetic polyurethane rigid (PUR) foam nanocomposites and investigation of thermal, mechanical, and sound absorption properties. (September 2019) - Moghaddam, Sahebeh Tamaddoni; Naimi-Jamal, Mohammad Reza
In this study, magnetic polyurethane rigid foam nanocomposites were synthesized by in situ polymerization of polyol and diisocyanate in the presence of ferroso-ferric oxide (Fe3 O4 )@silicon dioxide (SiO2 )@urea magnetic core-shell nanoparticles (NPs). The structure of the Fe3 O4 @SiO2 @urea NPs were confirmed by Fourier-transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, thermogravimetric analysis, and energy-dispersive X-ray spectroscopy. The effect of the Fe3 O4 @SiO2 @urea NPs on sound absorption characteristics, thermal stability, and mechanical property of the polyurethane (PU) foams was studied. The sound absorption coefficient was determined using the sound impedance tube method, and it was concluded that the coefficient of the composites was increased in comparison to the pure foam and previously reported magnesium hydroxide-3% and aluminum oxide-3% PU foams, over the entire frequency range.